Kontribusi Motivasi Belajar dan Penguasaan Kalimat Efektif terhadap Keterampilan Menulis Teks Ulasan Buku Mahasiswa Institut Payung Negeri - Suriadiman, Noprieka (GERAM, 2025)
The ability to write book reviews is an essential component of academic literacy that students, particularly in higher education, must possess. However, many students face difficulties in writing reviews in a coherent, concise, and communicative manner. This gap highlights a disparity between expected writing skills and students' actual abilities. This study aims to examine the contribution of learning motivation and mastery of effective sentence structures to students' book review writing skills at the Payung Negeri Institute. The research employs a quantitative method with a correlational approach. A sample of 40 students was selected using purposive sampling. The research instruments include a learning motivation questionnaire, a test of effective sentence mastery, and a book review writing assignment. The data analysis results reveal that learning motivation significantly contributes to writing skills, as does mastery of effective sentence structures. Additionally, both learning motivation and sentence mastery jointly have a significant impact on students' book review writing ability. The study concludes that enhancing writing skills is not only determined by technical linguistic aspects but also by affective factors such as learning motivation. Therefore, writing instruction should be designed integratively, considering both aspects.